CONSTRUCT - et værktøj til systemudvikling. Rapport nr. 1 - Jacobsen, Ole; Quistgaard, Claus (DAIMI Report Series, 1977)
This report introduces a new method for use in the first phase of the system-work, and also a tool for design of the structure of the data model is described. With background in Bachmann-diagrams and information graphs we have made a new graph - the CONSTRUCT graph. It can be used for description of the structure of the partial data models. For construction of the total data model we have made a language - the CONSTRUCT language. A CONSTRUCT description is used for two purposes: 1) to make the total description contain the information from the graph, and 2) to add attributes to the description. For more detailed description of the system, we will use the language DELTA. For that reason the CONSTRUCT language is very close to the DELTA language. In the report we also describe a text analyser which checks consistence between partial descriptions and makes a total description. The compiler between CONSTRUCT and DELTA is sketched